SINTESIS DAN UJI ANTIOKSIDAN SENYAWA (E)-1-(2-KLOROFENIL)-3-P-TOLILPROP-2-EN-1-ON - Rena Lestari, Eti Meirina Brahmana, (Menara Ilmu, 2018)
Halogen substituted analog compound chalcone(E)-1-(2-chlorophenyl)-3-ptolylprop-2-en-1-on was synthesized from 4-metylbenzaldehyde as aldehydes with 2-chloroacetophenone, as ketones by using aldol condensation reaction. The compoundresulted rendement with value of 60,08% and characterized by using UV, IR, MS, and1HNMR. Test of antioxidant activity using DPPH method showed that those compoundshave low potency as antioxidant agent LC50 with value 620,4506ppm.Keywords: Antioxidant, DPPH, Chalcone, dan Synthesis